STRUKTUR KOMUNITAS PLANKTON DI DANAU TAMBLINGAN KABUPATEN BULELENG BALI - Wadi, Fendria; Yusup, Deny Suhernawan; Suartini, Ni Made (SIMBIOSIS, 2021)
The purpose of this research was to determine the structure of the Tamblingan lake plankton community and community activities in the area around the lake and on the body. The methods used was survey methods and quantitative-descriptive methods. Survey method by visually observing the location based on the utilization of the lake area. The quantitative-descriptive method describes phenomena based on calculations and compared with ecological index. The results showed that the plankton composition consisted of five phyla dominated by the Chlorophyta phylum. Genus that was frequently found and in high abundance are Cosmarium, Staurastum, and Nitzshia. The abundance of plankton ranges from 5,757-11,197 cells/liter with the diversity index value (H') ranging from 1,38 to 1,76 which is classified as moderate, the uniformity index (E) ranges from 0.52-0.65 which is classified as moderate, the dominance index (C ) ranged from 0.35 to 0.48 indicating no dominance of a particular genus. Most of the community activities in the Tamblingan lake area are farmers and fishermen. Agricultural activity is very low so that it has no impact on the waters of Lake Tamblingan.